Knowledge of Prevention of Mother‐to‐Child Transmission of HIV and Associated Factors Among Pregnant Women in Debre Birhan, Ethiopia: A Community‐Based Cross‐Sectional Study - Lewegneh Wegayehu Tessema; Yazachew Moges Chekol; Elsa Awoke Fentie; Abebaw Addis Gelagay (Health Science Reports, 2026)
ABSTRACT Background and Aims Vertical transmission of HIV accounts for over 90% of pediatric HIV infections worldwide, making it a major public health concern. Maternal knowledge of mother‐to‐child transmission of HIV and its prevention is essential for the uptake of preventive measures and the success of elimination strategies. This study aimed to assess knowledge of prevention of mother‐to‐child transmission of HIV and associated factors among pregnant women in Debre Birhan, Ethiopia. Methods A community‐based cross‐sectional survey was conducted from June 2 to July 8, 2022 in Debre Birhan town. Participants were selected using a simple random sampling technique. Data were collected through a structured questionnaire, entered into Epi Data version 4.6, and exported to Stata version 17 for analysis. Prevalence ratios with 95% confidence intervals were estimated using Poisson regression with robust variance to identify factors associated with knowledge of PMTCT. Results Of 816 pregnant women, 803 provided complete information (response rate of 98%). Only 35.87% (95%CI = 32.62–39.25) of pregnant women demonstrated good knowledge of PMTCT. Factors associated with knowledge of PMTCT included residence, educational status, occupation, and receiving health information from healthcare providers. Conclusion Only 35% of pregnant women in Debre Birhan demonstrated good knowledge of PMTCT. Knowledge was significantly associated with residence, occupation, education, and receipt of health information from providers. These findings highlight the need for targeted interventions, including strengthened behavioral change communication through health extension workers and integration of PMTCT education into routine antenatal care, to support Ethiopia's HIV prevention goals.